Prevention and Treatment of Acute Respiratory Distress Syndrome by COVID-19: Role of Vitamin D on Immunomodulation and Renin-Angiotensin-Aldosterone System Regulation - Carmona, Maximiliano (2021)
The leading cause of complications or death from COVID-19 is due to the development of acute respiratory distress syndrome (ARDS). This syndrome is characterized by exacerbated inflammation, mainly at the pulmonary level, and an over-activation of the renin-angiotensin-aldosterone system (RAAS), usually culminating in death or permanent respiratory sequelae in the SARS-CoV-2 infected patients. In this sense, it has been proposed that vitamin D exerts numerous immunomodulatory effects by acting on various types of immune and epithelial cells, as well as being able to stimulate the protective arm (ACE2/Ang-(1-7)) and inhibit the harmful arm (ACE/Ang-II) of the RAAS. Therefore, some of the main mechanisms underlying these effects mediated by vitamin D and its receptors are discussed in the present review. The analysis of these mechanisms would positively influence the prevention and treatment of ARDS, thus preventing the progression of the disease and improving the prognosis of the patients.